BLOOD GLUCOSE AS A MARKER OF VENOUS THROMBOEMBOLISM IN CRITICALLY ILL CHILDREN - Tala, J. A. (2014)
BACKGROUND: The ability to predict the development of venous thromboembolism is highly desirable. OBJECTIVE: We aim to determine the association between hyperglycemia and venous thromboembolism in non-diabetic critically ill children. PATIENTS/METHODS: We conducted a retrospective cohort study that included children in the pediatric intensive care unit on vasopressor or on mechanical ventilator and without history of diabetes mellitus or prior diagnosis of thrombosis. Based on maximum blood glucose >150 mg/dl while admitted to the unit, children were categorized as hyperglycemic or non-hyperglycemic. Primary outcome was development of venous thromboembolism while admitted to the unit. We determined the association between hyperglycemia and venous thromboembolism using logistic regression models adjusting for selected subject characteristics. RESULTS: Of the 789 subjects analyzed, 34 subjects developed venous thromboembolism (incidence: 4.3%; 95% confidence interval: 3.0%–6.0%). Venous thromboembolism was more likely to develop in hyperglycemic subjects compared with non-hyperglycemic subjects. A total of 31 subjects (6.2%; 95% confidence interval: 4.2%–8.7%) developed venous thromboembolism after becoming hyperglycemic compared with 3 non-hyperglycemic subjects with venous thromboembolism (1.0%, 95% confidence interval: 0.2%–3.0%). When adjusted for age, diagnosis, presence of central venous catheter, prophylactic antithrombotic use and severity of illness, the odds ratio of venous thromboembolism with hyperglycemia was 4.1 (95% confidence interval: 1.2–14.1). For every 10 mg/dl increase in maximum blood glucose, adjusted odds ratio of venous thromboembolism was 1.04 (95% confidence interval: 1.01–1.06). CONCLUSION: Hyperglycemia is associated with venous thromboembolism in critically ill non-diabetic children. Maximum blood glucose is a potential predictor of venous thromboembolism in this population.